The Application of Biophysical Techniques to Study Antimicrobial Peptides. Issue 5 (11th July 2012) - Torcato Torcato, Inês M. Inês M.; Castanho Castanho, Miguel A. R. B. Miguel A. R. B.; Henriques Henriques, Sónia T. Sónia T.
Abstract : The increasing bacteria resistance to conventional antibiotics has led to the need for alternative therapies. Being part of the human innate defence system and with a broad spectrum of activity against bacteria, viruses, protozoa, and cancer cells, antimicrobial peptides (AMPs) are a very promising alternative. The mechanism of action of AMPs seems to broadly correlate with their ability to target the bacterial cell membrane. To understand and improve their effect, it is of major importance to unravel their mechanism of action and, in particular, to understand the peptide-membrane binding. Several biophysical techniques such as fluorescence spectroscopy, circular dichroism, zeta potential determination, and atomic force microscopy can be used to achieve this goal. Characteristics of AMPs-membranes interactions and the use of these biophysical techniques will be discussed.